2005
DOI: 10.1039/b505244k
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical rearrangement of dibenzo[1,4]dioxins proceeds through reactive spirocyclohexadienone and biphenylquinone intermediates

Abstract: Photochemical studies on a range of model dibenzo[1,4]dioxins were performed in aqueous and organic solutions. The compounds were found to undergo a photochemically initiated aryl-ether bond homolysis that yields reactive 2-spiro-6'-cyclohexa-2',4'-dien-1'-one and subsequent 2,2'-biphenylquinone intermediates. Under steady-state irradiation, the 2,2'-biphenylquinones were observed to participate in excited state hydrogen abstraction from the organic solvent to give the corresponding 2,2'-dihydroxybiphenyls. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…1 kcal/mol, and log K isom = 11.8), supporting prior experimental studies showing these compounds can be formed via the thermal intramolecular rearrangement of various 2,2 0 -diphenoquinones [7,9,13,14]. In contrast to the trans ?…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…1 kcal/mol, and log K isom = 11.8), supporting prior experimental studies showing these compounds can be formed via the thermal intramolecular rearrangement of various 2,2 0 -diphenoquinones [7,9,13,14]. In contrast to the trans ?…”
Section: Resultssupporting
confidence: 77%
“…In research efforts during the 1960s through 1980s, the groups of Hewgill [1][2][3][4][5][6][7] and Becker [8,9] employed oxidative approaches to generate-and in some cases isolate-these elusive compounds. More recently, during the 1990s and 2000s, it was shown that 2,2 0 -diphenoquinones may be photochemically generated from a range of dibenzo [1,4]dioxins (including the parent system) having electron withdrawing and donating groups [10][11][12][13], as well as via traditional thermal oxidative methods with 3,3 0 ,5,5 0 -tetraaryl substituents (e.g., phenyl and 4-methoxyphenyl) [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H and 13 C NMR was performed on a Bruker AV-400. 19 F MNR was performed on a Bruker DPX-250. MS was performed on an Agilent 6210 Time-of-Flight spectrometer.…”
Section: Generalmentioning
confidence: 99%
“…Chlorophenols, hydroquinone and pyrocatechol were from Aldrich. Dibenzodioxin was prepared by the method of Rayne et al [19]. Trifluoromethoxybenzenes 5-8 were prepared by the method of Feiring [2,10].…”
Section: Generalmentioning
confidence: 99%